Perdido - Collignon, Rick (Denver : MacMurray & Beck, 1997)
Twenty years earlier a white girl was found hanging from a bridge in a small town in New Mexico. The story arouses the curiosity of Will Sawyer, a new resident, and he decides to find out why. A study of curiosity, why some people have it and others don't.
Keywords: Man-woman relationships; Villages; Pastoral fiction